Does Reducing Unemployment Benefits During a Recession Reduce Youth Unemployment? Evidence from a 50% Cut in Unemployment Assistance - Aedin Doris; Donal O'Neill; Olive Sweetman (Institute of Labor Economics (IZA), 2017)
We use administrative data to examine the effect of a 50% benefit cut for young unemployed workers in Ireland during the Great Recession. Because the cut applied only to new benefit claims, claimants whose unemployment start dates differed by a matter of days received very different benefits; we exploit this fact in our Regression Discontinuity and Difference-in-Difference analyses. While we find no impact on unemployment duration for those aged 20 21, the benefit cut significantly reduced duration for 18 year olds, with an estimated elasticity close to one. We consider possible explanations for our findings and also examine long-run effects.
Keywords: J64; 330; unemployment assistance; labour supply; regression discontinuity